Learning Motivation and Learning Readiness on Science Learning Outcomes - Intan Nurcahayani; Rosita Endang Kusmaryani; Ahmad Chandra Jaya; Deananda Syafitri (LPPM Undiksha, 2025)
The main factor that hinders the improvement of student learning achievement is caused by the learning model that is still conventional. The learning model that is still conventional has an impact on low learning motivation. This has an impact on low student science learning outcomes. Based on this, this study aims to analyze and explain the influence of student learning motivation and readiness, both partially and simultaneously, on learning outcomes in Natural Sciences (IPA). This study uses a quantitative type with a correlational approach, and the research subjects amounted to 85 students from a population of 231 students. The data collection method used a scale instrument to measure learning motivation and readiness and a test to measure science learning outcomes. The data obtained were analyzed using normality tests, descriptive statistics, and multiple linear regression analysis. The study results showed that learning motivation and readiness significantly affected student science learning outcomes, with regression coefficients of 0.624 and 0.709, respectively. The t-test results showed a significance value of 0.000 for both variables. In conclusion, increasing motivation and learning readiness can improve student science learning outcomes. The implications of this study suggest the importance of developing motivation and learning readiness to improve student learning outcomes in science.